Provisional measures before international courts and tribunals - Miles, Cameron A., 1984- (Cambridge (UK) : Cambridge University Press, 2017)
"Since the decision of the International Court of Justice in LaGrand (Germany v. United States of America), the law of provisional measures has expanded dramatically both in terms of the volume of relevant decisions and the complexity of their reasoning. Provisional Measures before International Courts and Tribunals seeks to describe and evaluate this expansion, and furthermore to undertake a comparative analysis of provisional measures jurisprudence in a range of significant international courts and tribunals and ad-hoc interstate arbitration tribunals. The result is the first comprehensive examination of the law of provisional measures in ten years, and the first to compare investor-state arbitration jurisprudence with more traditional interstate courts and tribunals"--
Origins of provisional measures -- Constituent instruments and procedural rules -- Power to order provisional measures -- Purpose of provisional measures -- Prejudice and urgency -- Content and enforcement -- Questions of substance and procedure -- Litigation strategy and provisional measures.
Based on author's thesis (doctoral - Cambridge University, 2016).
Includes bibliographical references (pages 488-508) and index.
Keywords: Civil procedure (International law); Provisional remedies; Civil procedure (International law); Provisional remedies